2007
DOI: 10.1249/mss.0b013e31802fa679
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Pain in Retired Professional Football Players

Abstract: Retired professional football players experience levels of depressive symptoms similar to those of the general population, but the impact of these symptoms is compounded by high levels of difficulty with pain. The combination of depression and pain is strongly predictive of significant difficulties with sleep, social relationships, financial difficulties, and problems with exercise and fitness. A hypothesis explaining this association is that significant musculoskeletal disability and chronic pain interferes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 21 publications
4
127
1
1
Order By: Relevance
“…In two recent reviews of the literature, it was concluded that there is insufficient scientific evidence to conclude that CTE is a risk factor for suicide (Iverson, 2014;Wortzel et al, 2013). That said, former NFL players might be at increased risk for depression (Gonzalez et al, 2010;Schwenk et al, 2007), and their rate of chronic pain and opioid use is high (Cottler et al, 2011).…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent reviews of the literature, it was concluded that there is insufficient scientific evidence to conclude that CTE is a risk factor for suicide (Iverson, 2014;Wortzel et al, 2013). That said, former NFL players might be at increased risk for depression (Gonzalez et al, 2010;Schwenk et al, 2007), and their rate of chronic pain and opioid use is high (Cottler et al, 2011).…”
Section: Depressionmentioning
confidence: 99%
“…Moreover, former NFL players with depression and chronic pain are much more likely to report life stress and financial difficulty than former players without depression (Schwenk et al, 2007). Therefore, factors unrelated to CTE might place certain former athletes at increased risk for suicide.…”
Section: Depressionmentioning
confidence: 99%
“…95 % (N = 18) of players indicated worse sleep in the nights after night matches. Schwenk et al [6] showed that two of the most common retirement concerns reported by players are difficulty with pain (48 %) and trouble sleeping (28 %). Throughout their career, players are frequently exposed to various situations and conditions that can interfere with sleep, potentially leading to acute and chronic sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, minimal literature exists on the effect that orthopaedic injuries have on players in the long term. Schwenk et al 15 assessed the prevalence of depression and pain in retired professional football players, by using a self-reported survey method in members of the NFL Players Association. The most frequent problem reported was difficulty with pain, with 48% rating their pain as common to quite common.…”
Section: Health Conditions In Retired Nfl Playersmentioning
confidence: 99%